MondoA is highly overexpressed in acute lymphoblastic leukemia cells and modulates their metabolism, differentiation and survival - Wernicke, Caroline; Bandapalli, Obul Reddy (Leukemia research, 2012)
Acute lymphoblastic leukemia (ALL) is the most common childhood cancer. To identify novel candidates for targeted therapy, we performed a comprehensive transcriptome analysis identifying MondoA (MLXIP) - a transcription factor regulating glycolysis - to be overexpressed in ALL compared to normal tissues. Using microarray-profiling, gene-set enrichment analysis, RNA interference and functional assays we show that MondoA overexpression increases glucose catabolism and maintains a more immature phenotype, which is associated with enhanced survival and clonogenicity of leukemia cells. These data point to an important contribution of MondoA to leukemia aggressiveness and make MondoA a potential candidate for targeted treatment of ALL.
Gesehen am 26.11.2018